Intersubband absorption in Si‐ and Ge‐doped GaN/AlN heterostructures in self‐assembled nanowire and 2D layers. Issue 8 (15th March 2017) - Ajay, Akhil; Lim, Caroline B.; Browne, David A.; Polaczynski, Jakub; Bellet‐Amalric, Edith; den Hertog, Martien I.; Monroy, Eva
Abstract : GaN/AlN is a promising material system for the development of an ultrafast intersubband technology operating at telecommunication wavelengths, thanks to the large conduction band offset and sub‐picosecond intraband relaxation time. In this paper, we explore short wavelength infrared intersubband transitions occurring in the conduction band of GaN/AlN heterostructures in both planar and nanowire (NW) geometries. We study the effect of Si and Ge doping in both quantum wells and NW heterostructures using the same active region thickness and dopant concentration. We demonstrate that both Si and Ge are suitable dopant candidates at a concentration of mid‐10 19 cm −3 for the fabrication of intersubband devices based on planar and NW heterostructures.